Correlation of Inhibin A Serum Level with Preeclampsia - Dian Pratama (Indonesian Journal of Obstetrics and Gynecology, 2011)
Objective: The purpose of this research is to analyze the difference of Inhibin A serum level between preeclampsia patients with normal pregnant patients and to analyze the relation between Inhibin A serum level with preeclampsia. Method: Comparison of average Inhibin A serum level of the preeclampsia group with normal pregnancy was analyzed by using Mann-Whitney test, and the correlation between Inhibin A serum level and preeclampsia was using biserial point correlation test. Samples were obtained from blood of patient suffered preeclampsia and also normal pregnancy, each containing 17 samples according inclusion and exclusion criterias. Patients came to Hasan Sadikin Hospital and two satellite hospitals in August to November 2010. Result: Characteristic test in two groups of study showed that both groups were homogeny and could compared. Mean level of Inhibin A serum was higher in preeclampsia (1268.08 pg/ml) than normal pregnancy (911.12 pg/ml) (p = 0.042) there was a strong positive correlation between Inhibin A serum level with preeclampsia (r pbi = 0.354; p = 0.027). Conclusion: From this research, we can conclude that Inhibin A serum level in preeclampsia is higher than normal. There is a positive correlation of Inhibin A serum level with preeclampsia. [Indones J Obstet Gynecol 2011; 35-1: 36-9] Keywords: inhibin A serum, normal pregnancy, preeclampsia